2016
DOI: 10.1002/bit.26013
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analysis of essential binding sites on the promoter of the Serratia marcescens spn operon with the quorum‐sensing receptor SpnR

Abstract: The N-acylhomoserine lactone (AHL) receptor SpnR is a LuxR family protein that acts as a negative regulator of AHL-dependent quorum sensing (QS). SpnR binds to DNA in Serratia marcescens AS-1 via the spn box; however, the binding affinity of SpnR with the nucleotides on the spn box has not yet been investigated. In this study, we used an spn-box-modified sensor electrode, and quartz crystal microbalance analysis demonstrated a drastic reduction of the uptake of SpnR. The nucleotides G5 and C16 at the AHL-recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Moreover, the N-acylhomoserine lactone (AHL) receptor SpnR protein is a member in LuxR family that modulates S. marcescens QS. SpnR binds to S. marcescens DNA PLOS ONE on a lux-box like promoter to initiate a sequential QS process in the LuxR family [53]. In this context, it can be expected that the compounds which can regulate LuxI/LuxR system may have anti-QS activities, so then synthetic AHL analogues which inhibited Lux QS system were suggested as QS inhibitors [54].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the N-acylhomoserine lactone (AHL) receptor SpnR protein is a member in LuxR family that modulates S. marcescens QS. SpnR binds to S. marcescens DNA PLOS ONE on a lux-box like promoter to initiate a sequential QS process in the LuxR family [53]. In this context, it can be expected that the compounds which can regulate LuxI/LuxR system may have anti-QS activities, so then synthetic AHL analogues which inhibited Lux QS system were suggested as QS inhibitors [54].…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, we demonstrated the negative regulation of SpnR for the spn operon, which is related to the production of AHL-synthase and SpnR itself [8]. Specific interaction of SpnR with a promoter spn box was also proved in vitro by using a quartz crystal microbalance (QCM) analysis [9]. Fig.…”
Section: Introductionmentioning
confidence: 87%
“…The exchange of information between cells in an algae–bacteria system is conducted by quorum sensing, in which acyl-homoserine lactones (AHLs) are important signal molecules in the intercellular communication of gram-negative bacteria [ 19 ]. AHLs can affect bacteria activities, such as biofilm formation [ 20 , 21 , 22 ], pigment synthesis [ 23 ], and antibiotic synthesis [ 24 ]. Therefore, they play an important role in wastewater treatment technology [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%